An Examination of the Relationship Between Emotional Labour and Organisational Commitment: The Moderating Role of Leader-member Exchange (LMX) - Lee, Joon (Auckland University of Technology, 2017)
In the hospitality workplace, the frontline employees of a customer-contact work team are placed in the most stressful work environments. Given the demand for top-rated service performance expected from frontline employees, the success of achieving service excellence hinges upon their abilities to comprehend and manage considerable emotional challenges during service encounters. Although the extant literature on emotional labour has primarily highlighted its detrimental consequences, a substantial number of recent studies report that exerting emotional labour is often related to positive work outcomes. Although researchers agree that emotional labour has a mixed effect (both positive and negative), only a few studies have scrutinised the positive aspects of emotional labour. Positive emotions may be generated when employee makes a conscious effort to control their actual emotions and instead display the emotions that meet the expectations of both the customer and the organisation. Such effort can send positive signals indicating how much the employees are prepared to commit themselves to the organisation. Based on broaden-and-build theory, this study investigates the positive association of emotional labour with organisational commitment, which is a prominent employee outcome that indicates the level of an employee's devotion to the organisation. This study further examines Leader-Member Exchange (LMX) as a moderator between emotional labour and organisational commitment based on a social interaction model of emotion regulation and social exchange theory. The study adopted a quantitative survey research method to measure study variables and examine the relationships between them. The final sample contained 248 frontline food and beverage employees in seven different hotels in Seoul, South Korea, and a series of hierarchical regression analyses were used to test research hypotheses. The key findings of this study are as follows. First, both emotional effort and emotional dissonance had a significant impact on the organisational commitment of employees. Second, LMX moderated the relationship of the subordinates’ emotional dissonance, which is a dimension of emotional labour with organisational commitment, whereas the relationship of emotional effort, the other dimension of emotional labour with organisational commitment, was not moderated by LMX. This study is among the first attempts to empirically examine the relationship between emotional labour and organisational commitment, where LMX is thought to act as a moderator in the hotel context. The implications of the findings are discussed for both researchers and practitioners.
Keywords: Emotional labour; Emotional effort; Emotional dissonance; Organisational commitment; Leader-Member Exchange